2020
DOI: 10.1159/000512746
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Cirrhosis: Changing Trends in Etiology Over the Years

Abstract: Background and goals: The aims of the present study were to investigate the natural history of cirrhosis and to determine trends in the etiology of cirrhosis. Methods: Between January 2001 and January 2018, a total of 1341 patients had been diagnosed with cirrhosis were included. Results: A total of 898 cirrhotic patients, who were followed for at least six months were included into the analysis. The median age was 54 years. The median Child-Pugh and MELD scores were 7.5 and 11, respectively. Ascites (51%) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…[12,13] A recent study in Turkey reported that NAFLD was one of the most common causes of cirrhosis, accounting for 8.5% of cases. [15] In the present study, 33% of the HCC patients were obese, 30% had DM, and 36% had hypertension. NAFLD-related cir- rhosis was one of the most frequent causes of HCC, accounting for 10% of cases.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…[12,13] A recent study in Turkey reported that NAFLD was one of the most common causes of cirrhosis, accounting for 8.5% of cases. [15] In the present study, 33% of the HCC patients were obese, 30% had DM, and 36% had hypertension. NAFLD-related cir- rhosis was one of the most frequent causes of HCC, accounting for 10% of cases.…”
Section: Discussionsupporting
confidence: 46%
“…[6] In Turkey, HBV and HCV infections remain major causes of liver-related morbidity and mortality and the most common causes of cirrhosis and HCC in more than 50% of HCC cases. [7][8][9][10][11][12][13][14][15] The data regarding the etiologic and clinical characteristics of HCC in a large cohort of Turkish patients are limited. The aim of the present study was to examine the etiology of HCC by underlying cause and to determine the characteristics and clinical features of patients with HCC in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…14 Studies have shown that HCV is the second most common cause of both liver cirrhosis and HCC in Turkey. 15,16 Today, HCV infection is a disease that can be successfully treated. With the use of DAA drugs, the success rate in the treatment of HCV infection has improved tremendously.…”
Section: Discussionmentioning
confidence: 99%
“…HCV enfeksiyonu; erken döneminde asemptomatik olduğu için sinsi seyirli, enfekte olanların %60-80'inin kronikleştiği, karaciğer sirozunun ve hepatosellüler karsinomun (HCC) en sık sebeplerinden biridir. HCV'nin hem karaciğer sirozunun hem de HCC'nin Türkiye'de 2. sık sebebi olduğu yapılan çalışmalarla ortaya konmuştur (2,8). HCV enfeksiyonu günümüzde başarı ile tedavi edilebilen bir hastalıktır.…”
Section: Discussionunclassified